Decolonising Blue Spaces in the Anthropocene 2021
DOI: 10.1007/978-3-030-61071-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Justice and Indigenous Environmental Justice

Abstract: In this chapter we provide a broad overview of three dominant ways environmental justice is framed within the scholarship and consider how Indigenous peoples’ understanding and demands for environmental justice necessitate a decolonising approach. Despite critiques, many scholars and policymakers still conceive of environment justice through a singular approach (as distributive equity, procedural inclusion, or recognition of cultural difference). Such a narrow reading fails to appreciate the intersecting and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 113 publications
0
9
0
2
Order By: Relevance
“…Instead, the Foundation's power to influence governing norms and institutions is an indirect means of steering that involved filling monetary gaps that mobilized and galvanized other local governance actors and networks, a process sometimes referred to as “orchestration” (Abbott et al, 2016). Other environmental governance literatures on field‐building (Bartley, 2007; Phillips, 2018), agency (Betsill & Milkoreit, 2020), meta‐governance (Hooge et al, 2021), polycentricity (Carlisle & Gruby, 2019a) and environmental justice (Bennett, 2018; Bennett et al, 2021; Parsons et al, 2021) are ripe for engaging important questions of rights, sovereignty, and power in conservation philanthropy.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the Foundation's power to influence governing norms and institutions is an indirect means of steering that involved filling monetary gaps that mobilized and galvanized other local governance actors and networks, a process sometimes referred to as “orchestration” (Abbott et al, 2016). Other environmental governance literatures on field‐building (Bartley, 2007; Phillips, 2018), agency (Betsill & Milkoreit, 2020), meta‐governance (Hooge et al, 2021), polycentricity (Carlisle & Gruby, 2019a) and environmental justice (Bennett, 2018; Bennett et al, 2021; Parsons et al, 2021) are ripe for engaging important questions of rights, sovereignty, and power in conservation philanthropy.…”
Section: Discussionmentioning
confidence: 99%
“…While our review notes that industry, government, and the scientific community acknowledge the importance of Indigenous inclusion (Arquette et al, 2002; Ellison, 2012; Gover, 2007; Holifield, 2012; Michelsen, 2010; Nolan, 2009; Sistili et al, 2006), we found minimal evidence of Indigenous leadership in the management of contaminated sites. Recent literature from Indigenous scholars on natural resource management describes that the inclusion of and collaboration with Indigenous peoples in environmental management is often tokenistic (Parsons et al, 2021). The contribution of Indigenous voices in contaminated site management often occurs too late in the federal process, which perpetuates the “downstream” approach to site management discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The writer further maintains that the term incorporates 'environmental racism' and 'environmental classism,' which captures the idea that different racial and socioeconomic groups experience differential access to environmental quality. Scholars also argue that racism plays a critical factor in environmental planning and decision-making processes in the US and other settler nations (Parsons et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%